To solve this problem you must apply the proccedure shown below:
1. You need to apply the Pythagorean Theorem:
![c^(2)=b^(2)+a^(2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/mcmcmtncd82yump30vq7vc5ik8ueegjsr9.png)
Where c is the hypotenuse and the legs are a and b.
2. Now, you must substitute the values given in the problem above and solve for b:
![(2b)^(2)=b^(2)+12^(2)\\4b^(2)=b^(2)+144\\4b^(2)-b^(2)=144\\3b^(2)=144\\b=\sqrt{(144)/(3)}\\b=6.92](https://img.qammunity.org/2019/formulas/mathematics/middle-school/wyxbi6ei5duunm1gpimg9x5e0939dq6id9.png)
Therefore, the answer is: The value of b is 6.92